The Role of Information and Communication Technology in Improving the Financial Performance of Banks (An applied study on commercial banks in the eastern region of Libya (Sebha University Conference Proceedings, 2024)
This study aimed to test and determine the extent to which bank departments understand and realize the importance of the concept of information and communications technology and to know the extent of its use to improve the financial performance of Libyan commercial banks whose main management is located in the eastern region. To achieve the goal of the study, one main hypothesis and two sub-hypotheses were formulated, and the study population consisted of department managers. finance, employees in financial departments, and internal auditors in Libyan commercial banks. The study sample was limited to public commercial banks whose main departments are located in the eastern region. The study relied on the questionnaire method as a tool for collecting the necessary data, as a number of (55) questionnaire forms were distributed, of which (50) valid questionnaire forms were received for analysis. The study used both descriptive statistics and inferential statistics to analyze the data, relying on the statistical program SPSS (23). The study found that there is an understanding and awareness among bank managements of the necessity to use ICT, given the time, effort, and cost savings these systems, programs, and applications offer in accomplishing required tasks and services with accuracy, reliability, transparency, and quality. ICT also contributes to increasing the effectiveness of the accounting system by preparing and presenting financial reports promptly and in a manner that ensures improved financial performance. The study recommended keeping pace with developments in the use of ICT tools and methods. The Central Bank of Libya and all regulatory bodies should monitor how commercial banks use ICT as an essential means to improve financial performance. It also recommended that the managements of commercial banks allocate budgets to keep up with the ongoing updates in ICT, stay updated with the latest infrastructure developments,